TOCAP (TOGA EDUCATION PROGRAM) MELALUI PENINGKATKAN PENGAJARAN EDUKATIF TENTANG PENERAPAN HIDUP SEHAT PADA SEKOLAH DASAR DI KEDIRI - Dian Harniawati; Krisnawati Krisnawati; Tri Yulian Widya (Universitas Sebelas Maret, 2014)
Herbal Plants (Toga) are plants which have been used as herbal medicine. These plants have the ability to synthesize a wide variety of chemical compounds that are used to perform important biological functions, and to defend against attack from predators such as insects, fungi and herbivorous mammals. Therefore, they have beneficial effects on long-term health when consumed by humans, and can be used to effectively treat human diseases. Even though, herbal can be used to treat human diseases, many people prefer to consume drug that may have bad effect for a long time consuming. In order to introduce the beneficial of herbal plant and realize many people to use herbal plants that can be found in the garden, TOCAP is very crucial to be done at early age. In doing so, the writers introduce TOCAP for elementary school students. TOCAP is training and educative teaching consider with utilization of herbal plants which covers creating media plant, making a fertilizer, technical how to plant herbal plant, the advantages of herbal plant , and how to make herbal medicine. The steps of TOCAP include preparation, the introduction about TOCAP, training, guiding, monitoring, and evaluation. Furthermore, this research gives beneficial experience for the student to learn about how to utilize herbal plant that they found around them to increase healthy life style. Keywords: TOCAP, educative teaching, healthy life